New hipparionine fossils from the Dhok Pathan Formation of Punjab, Pakistan. (3rd July 2022) - Aftab, Kiran; Khan, Muhammad Akbar; Babar, Muhammad Adeeb; Abbas, Syed Ghyour; Ghaffar, Abdul; Akhtar, Muhammad; Iqbal, Riffat; Afsheen, Sumera
ABSTRACT: We visited several late Miocene to early Pliocene localities of the Dhok Pathan and Naragghi villages in the Chakwal district of Punjab, Pakistan and recovered a comprehensive collection of hipparionine fossils. The recently recovered specimens from these localities are compared to the previously collected material of the Middle Siwalik Hipparionini, allowing for the identification of four types of hipparionines: Cormohipparion, Sivalhippus, Hipparion, and Hipparionini indet. The hipparionine horses are common elements of the late Miocene to early Pliocene of the Siwalik Group in Pakistan.